Democratisation in Malaysia: towards gender parity in political participation - Rashila Ramli (Universiti Kebangsaan Malaysia, 1998)
This paper focuses on the partnership between men and women within the realm of political participation using Malaysia as a case study. Data is accumulated quantitatively and qualitatively. In Malaysia, women have been involved in politics even prior to Independence. However, there is a tendency for women to play a supportive role rather than that of a decision-maker. Thus, at present, there is a lack of parity between men and women in politics. Research shows that women's political participation is impacted by the social construction of gender and ethnicity, creating a number of obstacles for women when they operate in the public sphere. While empirical data shows that more women are entering politics, it is argued that the democratization process has been constrained by societal values.